Even low light pollution levels affect the spatial distribution and timing of activity of a "light tolerant" bat species. (15th July 2022) - Mariton, Léa; Kerbiriou, Christian; Bas, Yves; Zanda, Brigitte; Le Viol, Isabelle
Abstract : By disrupting nocturnal landscapes worldwide, light pollution caused by Artificial Light At Night (ALAN) is recognized as a major threat to biodiversity. As even low light intensities might affect some taxa, concerns are arising about biological responses to widespread low light levels. We used data from a French citizen science bat monitoring program (1894 full-nights monitored on 1055 sites) to explore the landscape-scale effects of light on an open-space-foraging bat species, the Serotine bat ( Eptesicus serotinus ). We assessed this species' abundance and timing of night-time activity (median time of activity) at foraging sites. ALAN, and to a lesser extent moonlight, reduced E. serotinus abundance. ALAN delayed activity, and this delay was amplified during overcast nights. On the contrary, where there was no ALAN, the higher the cloud cover, the earlier the activity occurred. Cloud cover likely darkened the night sky in rural locations, whereas it amplified skyglow in light-polluted places, increasing ALAN effects on bats. Interestingly, moonlight also delayed activity but this effect was weakened where there was ALAN. Our study shows that even fine variations of light levels could affect the spatiotemporal distribution of a common species usually considered to be "light tolerant", with potential cascading effects on individual fitness and population dynamics. It stresses how urgent it is to preserve and restore dark areas to protect biodiversity from light pollution while working on light intensity and directivity where ALAN is needed. Graphical abstract: Image 1 Highlights: Light pollution decreases bat abundance and delays their timing of activity. Even low light levels affect bat abundance and timing of activity. Skyglow enhanced by cloud cover increases light impact on the timing of activity. Light pollution can even affect "light tolerant" open-space-foraging bat species. Reducing direct and indirect light pollution at landscape scale is an urgent need.